Modals in English and Arabic Legal Texts - Al-Mahjoob, Nawwaf Mohammed Abdulla (جامعة تكريت - كلية الآداب, 2016)
تعد الأفعال الساندة موضوعًا بالغ الأهمية في اللغة القانونية الإنكليزية لما لها من دور في التعبير عن المعنيين الأساسيين في القانون وهما الإلزام والجواز. تذهب هذه الدراسة إلى إن موضوع ترجمة الأفعال الساندة لم يلق ما يستحق من اهتمام من الباحثين، لهذا تعتبر الدراسة محاولة للبحث في هذه الأفعال في النصوص القانونية من منظور عابر للثقافات. لقد تم اختيار "اتفاقية مناهضة التعذيب وغيره من ضروب المعاملة أو العقوبة القاسية أو اللاإنسانية أو المهنية" لتشكل البيانات التي تمثل اللغة القانونية الإنكليزية. وقد تمت دراسة كل فعل من هذه الأفعال الساندة بشكل منفصل على أساس انتشارها (عددها) ومعناها ومكافئها في اللغة العربية وقد توصلت هذه الدراسة إلى أن الأفعال الساندة في اللغة القانونية الإنكليزية تختلف عن نظيراتها في اللغة الإنكليزية العامة من حيث الانتشار والمعنى ومكافئها في اللغة العربية فمثلاً يعتبر الفعل الساند "Shall" الأكثر شيوعًا في اللغة القانونية الإنكليزية بينما يعتبر الأقل شيوعًا في اللغة الإنكليزية العامة. أما من ناحية المعنى فإن معنى الفعل الساند "Shall" في اللغة القانونية يختلف عنه في اللغة الإنكليزية العامة فهو في اللغة القانونية يفيد الإلزام بينما يفيد الدلالة إلى المستقبل في اللغة الإنكليزية العامة. إضافة إلى ذلك فإن هذه الدراسة توصلت إلى أنه رغم عدم وجود مكافئ بعينه للفعل الساند "Shall" في اللغة العربية إلا أن معنى الإلزام الذي يفيده هذا الفعل يعبر عنه في اللغة العربية من خلال الفعل الرئيسي المضارع الذي يتبع "Shall" وتوصلت الدراسة أيضًا إلى أن الفعل الساند "may" يترجم إلى العربية بالفعل "يجوز" عندما يفيد "الرخصة" ويترجم إلى "قد" عندما يفيد "الاحتمالية"، وأخيراً أن الأفعال الساندة "can" و "would" و "Should" نادرة الوجود في بيانات الدراسة أما بقية الأفعال الساندة "could" و "might" و "must" و "will" فليس لها وجود البتة.
Modal verbs are treated as a paramount point in legal English because they are used to convey the two basic meanings in legal language: obligation and permission. It is argued that the translation of modals in legal texts has received little attention in Arabic. As such, this paper is an attempt to account for the translation of English central modal auxiliaries in a legal text into Arabic from a cross-cultural perspective. The legal text selected to represent the data of the study is "The Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment". For this purpose, each modal is dealt with separately in terms of the distribution, meaning, and the Arabic equivalent used to convey its meaning. It is found that modals in legal English exhibit important differences from modals in general English as regards their meaning distribution and . The modal "shall", for instance, is the most frequent modal in legal English, whereas it is the least frequent modal in non-legal English. Moreover, semantically, the meaning of "shall" differs according to the text type it occurs in: it expresses obligation in legal English and futurity in non-legal English. Also, one of the conclusions of the study is that the modal "shall" has no lexical equivalent in Arabic. However, when it expresses obligation, its meaning is achieved in Arabic via the main verb of the sentence. Further, the study reveals that the modal "may" is quite frequently rendered into Arabic as "يجوز" when it implies permission; while it is rendered as "قد" when it implies possibility. Finally, the modal verbs "can", "would", "should" hardly occur in legal texts; while the remaining modals, "could", "might", "must", "will", have no occurrence in the data.
Keywords: اللغة العربية -- اللغة الإنجليزية -- القواعد اللغوية -- الأفعال الساندة